Pengaruh Brand Awareness, Perceived Quality Dan Harga Terhadap Keputusan Pembelian Pada Labore Eatery Coffee Kota Malang - Nadia Surya Safitri; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This studyied aimed to determine the effects of brands images, the product’s qualities and priced on product purchased decision’ Labore Eatery Coffee Malang City. The location of this research was carried out on Labore Eatery Coffee who became consumers of Labore Eatery Coffee Malang City. This research is a quantitative research. This research uses a case study method where data is obtained by distributing questionnaires to Labore Eatery Coffee who were selected by purposive sampling. Determination of the number of samples using the Maholtra formula and the results obtained were 95 respondents. Data were analyzed using multiple linear regression test and determination test. Based on the results of data analysing of the result to the F test indicate that brands imaged, producted qualitied and priced have a significant dan positive effects on purchasing decisions and affect purchasing decisions for Labore Eatery Coffee products in Malang City. Furthermore, the resulting of the point of t-test indicates that branding imaged, producting qualities and priced partially have significant and positive effecting on purchased decisioned to Labore Eatery Coffee products in Malang City. The results of the determination test show that the percentage is 69.1%, which is where purchasing decisions can be influenced by brand image, product quality and price. Management should pay more attention to consumer attitudes and behavior in the purchase stage, one of which is by providing good quality products so that consumers will easily buy Labore Eatery Coffee products more precisely and quickly. Keywords: Purchase Decision, Brand Awareness, Perceived Quality, Price